Correlation between Physical Properties and Specific Fuel Consumption in Jatropha -Used Cooking Oil Biodiesel Mixtures - Wahyudi, Wahyudi; Nadjib, Muhammad; Apriyanto, Apriyanto (Universitas Muhammadiyah Yogyakarta, 2023)
This study was motivated by the need to understand the influence of using waste jatropha biodiesel on the physical properties of fuel and the performance of diesel engines. The primary aim was to determine the relationship between the fuel's physical properties, spray angle, and specific fuel consumption (SFC) at various load levels. The methodology employed included measurements of density, viscosity, flash point, calorific value, spray angle, and SFC for different blends of waste jatropha biodiesel and diesel (B5, B10, B15, B20). The research results demonstrate an increase in density, kinematic viscosity, and flash point, along with a decrease in calorific value, as the biodiesel content increases. The density of the biodiesel mixture ranges from 823 kg/m³ at B5 to 836.50 kg/m³ at B20. The kinematic viscosity increases from 3.9 cSt at B5 to 5.2 cSt at B20, and the flash point rises from 112.9°C at B5 to 128.7°C for B20. Meanwhile, the calorific value decreases from 10308.2670 cal/g at B5 to 10133.8280 cal/g for B20. A strong correlation exists between density and kinematic viscosity with the spray angle, exhibiting R2 values of 0.9141 and 0.8287, respectively. The correlation between the fuel's physical properties and the specific fuel consumption (SFC) is also substantial, marked by high R2 values above 0.93. These findings provide a solid foundation for the development of more optimal biodiesel formulations.